COGNITIVE-BEHAVIORAL COUNSELING TO IMPROVE ACADEMIC ACHIEVEMENT IN AN ISLAMIC BOARDING SCHOOL: A QUASI-EXPERIMENTAL STUDY - Veny Kurnia; Weni Kurnia Rahmawati; Nailul Fauziyah (CV. TOTUS TUUS, 2026)
Academic underachievement among mahasantri in Islamic boarding schools is frequently associated with maladaptive cognitions, low learning motivation, weak study discipline, and ineffective time management, which collectively contribute to declining academic performance. This study aimed to examine the effectiveness of cognitive-behavioral counseling (CBC) in improving mahasantri’s academic achievement in a pesantren-based educational setting. A quasi-experimental nonequivalent control group design was applied, involving an experimental group receiving CBC and a comparison group without intervention, with pretest and posttest measurements administered using a questionnaire capturing indicators of academic problems (academic “decadence”) and achievement-related behaviors. Pre–post changes in the experimental group were analyzed using the Wilcoxon signed-rank test. The results showed that most participants in the experimental group demonstrated improved academic outcomes after counseling; Wilcoxon ranks indicated 28 positive ranks, 7 negative ranks, and 0 ties, with statistical significance (p < .05). The findings support the conclusion that CBC is a promising guidance-and-counseling strategy to strengthen academic achievement in pesantren contexts by helping students identify and restructure irrational thoughts and adopt more adaptive learning behaviors. Practically, counselors and pesantren administrators may integrate CBC sessions to enhance motivation, discipline, and academic self-beliefs. Future research should employ randomized or well-matched group designs, include longitudinal follow-up, and use mixed-method approaches to clarify mechanisms of change.